El profesor Dr. Robert Alexy fue investido como doctor honoris causa por la UBA - Universidad de Buenos Aires. Facultad de Derecho (2008)
"Originally published in Derecho al Día, Year VII, No. 136, Faculty of Law, University of Buenos Aires, November 2008."